Improvements of femto‐base station resource utilisation and ABS assignment convergence for dynamic ABS assignment. Issue 3 (1st February 2017) - Ozawa, Masayoshi; Ohtsuki, Tomoaki
Abstract : Almost blank subframe (ABS) techniques emerge as inter‐cell interference mitigation techniques in time region. One of the conventional ABS techniques is dynamic ABS assignment, which is able to adapt to interference state to protect the outage users more. However, the number of ABS assignments increases to protect a lot of outage users in the dense BS deployment. Therefore, the resource utilisation of base stations (BSs) decreases. Moreover, the convergence time of subframe assignment should be short enough to adapt to the change of environments. In this study, the authors propose a dynamic ABS assignment method to improve the resource utilisation of BSs and the convergence time of subframe assignment. Each BS receives feedback from surrounding BSs and users, and selects its subframe assignment based on the received feedback. Simulation results show that the proposed method improves the resource utilisation of BSs and the convergence time of subframe assignment compared with the conventional dynamic ABS assignment one, while achieving a similar user outage ratio.